Worldwide inertia to the use of cardiorenal protective glucose-lowering drugs (SGLT2i and GLP-1 RA) in high-risk patients with type 2 diabetes - Schernthaner, Guntram; Shehadeh, Naim; Ametov, Alexander S; Bazarova, Anna V; Ebrahimi, Fahim; Fasching, Peter; Janež, Andrej; Kempler, Péter; Konrāde, Ilze; Lalić, Nebojša M; Mankovsky, Boris; Martinka, Emil; et al. (Cardiovascular diabetology, 2020)
The disclosure of proven cardiorenal benefits with certain antidiabetic agents was supposed to herald a new era in the management of type 2 diabetes (T2D), especially for the many patients with T2D who are at high risk for cardiovascular and renal events. However, as the evidence in favour of various sodium-glucose transporter-2 inhibitor (SGLT2i) and glucagon-like peptide-1 receptor agonists (GLP-1 RA) accumulates, prescriptions of these agents continue to stagnate, even among eligible, at-risk patients. By contrast, dipeptidyl peptidase-4 inhibitors (DPP-4i) DPP-4i remain more widely used than SGLT2i and GLP-1 RA in these patients, despite a similar cost to SGLT2i and a large body of evidence showing no clear benefit on cardiorenal outcomes. We are a group of diabetologists united by a shared concern that clinical inertia is preventing these patients from receiving life-saving treatments, as well as placing them at greater risk of hospitalisation for heart failure and progression of renal disease. We propose a manifesto for change, in order to increase uptake of SGLT2i and GLP-1 RA in appropriate patients as a matter of urgency, especially those who could be readily switched from an agent without proven cardiorenal benefit. Central to our manifesto is a shift from linear treatment algorithms based on HbA1c target setting to parallel, independent considerations of atherosclerotic cardiovascular disease, heart failure and renal risks, in accordance with newly updated guidelines. Finally, we call upon all colleagues to play their part in implementing our manifesto at a local level, ensuring that patients do not pay a heavy price for continued clinical inertia in T2D.
Keywords: klinické rozhodování; kardiovaskulární nemoci; agonisté receptoru pro glukagonu podobný peptid 1; regulace glykemie; Humans; Glycemic Control; Sodium-Glucose Transporter 2 Inhibitors; ochranné faktory; nemoci ledvin; Incretins; rizikové faktory; Cardiorenal protection; výsledek terapie; Protective Factors; lidé; Biomarkers; Blood Glucose; Clinical inertia; Diabetes Mellitus, Type 2; medicína založená na důkazech; Practice Guidelines as Topic; biologické markery; Cardiovascular Diseases; Clinical Decision-Making; krevní glukóza; Type 2 diabetes; Treatment Outcome; glifloziny; směrnice pro lékařskou praxi jako téma; Practice Patterns, Physicians'; lékařská praxe - způsoby provádění; inkretiny; Global Health; Risk Assessment; celosvětové zdraví; Glucose lowering drugs; Glucagon-Like Peptide-1 Receptor Agonists; diabetes mellitus 2. typu; hodnocení rizik; Kidney Diseases; Evidence-Based Medicine; Risk Factors